The influence of internal and external factors in the rise and course of the Syrian civil war - Осадча, Я. Д. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
In this article the peculiarities of the armed conflict in Syria as a “new war” are considered. Moreover, the conflict is described as a proxy and hybrid warfare. Special attention is paid to the interaction between internal and external factors in the Syrian uprising and its influence on the possibility of either violent or political settlement of the conflict.